PENGARUH MODEL RADEC DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS V SD - Oktavia, Winda; Amsari, Dina; Suhartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning motivation and critical thinking skills of fifth-grade elementary school students. Students experienced difficulties in analyzing questions and providing correct answers, while classroom learning activities were predominantly teacher-centered, resulting in low student engagement and motivation. This study aimed to determine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model and learning motivation on the critical thinking skills of fifth-grade elementary school students.This research employed a quasi-experimental design. The sample was selected using a simple random sampling technique. Research instruments consisted of questionnaires to measure students’ learning motivation and tests to assess critical thinking skills. Data were analyzed using normality and homogeneity tests as prerequisite analyses. Hypothesis testing was conducted using independent sample t-tests for the first, second, and third hypotheses, while a two-way ANOVA was used to test the fourth hypothesis.The results showed that: (1) there was no significant difference in the critical thinking skills of students with high learning motivation between the experimental and control groups (Sig. = 0.430 > 0.05); (2) there was no significant difference in the critical thinking skills of students with low learning motivation between the experimental and control groups (Sig. = 0.660 > 0.05); (3) there was a significant difference in critical thinking skills between students in the experimental and control groups, with the experimental group achieving higher scores (Sig. = 0.001 < 0.05); and (4) there was no interaction effect between the RADEC learning model and learning motivation on students’ critical thinking skills, as indicated by the two-way ANOVA result (Sig. = 0.937 > 0.05).